The Analysis of Factor Affecting to the Hypertension Sympthom in Pre-Elderly of Selomerto 2 Health Center Wonosobo Regency - Permadani, Intan; Woro Kasmini Handayani, Oktia Oktia; Laksono, Budi (Public Health Perspective Journal, 2019)
Based on observational data and the introduction of Wonosobo District Health Office ofshowed that most non-communicable diseases are hypertension with the total number is20.987 (Wonosobo District Health Ofiice, 2017).Hypertension cases in District Health Office ofSelomerto 2 Wonosobo is because of people's lifestyles are less healthy, because of low attitudes, knowledge, stress and behavior pre elderly living on the prevention of hypertension. The purpose of this study was to analyze the factors that affect the incidence of hypertension in the elderly Pre Health Center Selomerto 2 Wonosobo 2018. This study is an analytic correlation with cross sectional approach. The samples were 150 respondents drawn at PHC Selomerto 2. The instrument used was a questionnaire and checklist. The data analysis was done by linear regression. The results showed (1) There is an effect against the hypertension attitude with p-value 0.017 <Î± (0.05). (2) There is the influence of knowledge about hypertension with p-value 0.039 <Î± (0.05). (3) There is an effect of stress on hypertension with a p-value of 0.021 <Î± (0.05), (4) There is affecting the behavior of the incidence of hypertension with a p-value 0.028 <Î± (0.05). Community must adopt a healthy lifestyle, while the Department of Health and local government should conduct a comprehensive health counseling.